2020
DOI: 10.3390/ma13235413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sintering Temperature Variation on Synthesis of Glass-Ceramic Phosphor Using Rice Husk Ash as Silica Source

Abstract: In this study, the authors attempted to propose the very first study on fabrication and characterization of zinc-boro-silicate (ZBS) glass-ceramics derived from the ternary zinc-boro-silicate (ZnO)0.65(B2O3)0.15(RHA)0.2 glass system through a conventional melt-quenching method by incorporating rice husk ash (RHA) as the silica (SiO2) source, followed by a sintering process. Optimization of sintering condition has densified the sintered samples while embedded beta willemite (β-Zn2SiO4) and alpha willemite (α-Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…It has excellent luminescence properties in blue, green and red spectral regions [14]. On the other hand, when heat treatment is applied, zinc silicate can be formed [15][16][17]. Zinc silicate has emerged as a good host material in plasma display panels, cathode ray tubes, laser crystal and electroluminescent devices [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It has excellent luminescence properties in blue, green and red spectral regions [14]. On the other hand, when heat treatment is applied, zinc silicate can be formed [15][16][17]. Zinc silicate has emerged as a good host material in plasma display panels, cathode ray tubes, laser crystal and electroluminescent devices [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…37–1485, JCPDS), indicating that the crystal structure of the samples is consistent with that of Zn 2 SiO 4 . The sharp diffraction peaks observed at 2θ = 12.60, 21.88, 25.32, 31.34, 33.85, 38.70, 48.64, and 65.40° correspond to the (011), (300), (220), (113), (140), (223), (333), and (713) crystal planes of Zn 2 SiO 4 , respectively. , The doping of the Mn ions does not alter the initial crystal structure of the Zn 2 SiO 4 material. The incorporation of Mn ions led to an increase in the intensity of the diffraction peaks of the Mn–Zn 2 SiO 4 material shown in Figure b, indicating an improvement in crystallinity and an increase in grain size.…”
Section: Resultsmentioning
confidence: 87%
“…38 This peak is attributed to the vibrational deformation of the Zn−O bond in the arrangement of the silicate zinc structure caused by the doping 223), (333), and (713) crystal planes of Zn 2 SiO 4 , respectively. 42,43 The doping of the Mn ions does not alter the initial crystal structure of the Zn 2 SiO 4 material. The incorporation of Mn ions led to an increase in the intensity of the diffraction peaks of the Mn−Zn 2 SiO 4 material shown in Figure 2b, indicating an improvement in crystallinity and an increase in grain size.…”
Section: Structure and Morphologymentioning
confidence: 99%
“…However, the presence of silica provides pozzolanic characteristics, which has allowed it to be studied as a cement additive for civil engineering applications, increasing the strength and durability of the material (Moayedi et al 2019). In addition to being used as raw materials for the synthesis of ceramic materials (Wahab et al 2020). On the other hand, other research has shown the applicability of rice husk ash as a sorbent in the extraction of antibiotics in solid phase (Grefa et al 2023).…”
Section: Environment Assessmentmentioning
confidence: 99%